Comprehensive Obstetric and Neonatal Emergency Services (PONEK) to Reduce Infant Mortality and Improve Maternal Health - Irawan Sastradinata (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
The Millennium Development Goals (Millennium Development Goal's) in2015, there are two targets and indicators that are specifically related tothe health of mothers, infants and children. The Millennium DevelopmentGoal's (MDG's) are for the hospital to implement the PONEK program(Comprehensive Obstetric Neonatal Emergency Services) for reduce infantmortality and improve maternal health. Maternal and perinatal servicesmust be organized in a teamwork and integrated between medical, nursing,midwifery and support services. The hospital as a health serviceorganization for the community needs to make continuous qualityimprovement, which continuously improves performance andservice quality in order to meet the demands of consumers and thehospital environment.